Effectiveness of Ethanol Extract Dosage of Arabian Bidara Leaf (Zizphus spina-christi (L.) Desf.) on Reduction of Hypercholesterolemia in Mus musculus - Valenata Valenata; Gaby Ayu Patricia; Khoirul Ngibad (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
Hypercholesterolemia is one of the main risk factors for cardiovascular disease, which is characterized by increased cholesterol levels in the blood. The leaves of Ziziphus spina-christi (Arabian bidara) are known to contain flavonoids, saponins, tannins, and alkaloids that have the potential to provide antihypercholesterolemia effects. This study aimed to evaluate the effectiveness of ethanol extract of Z. spina-christi leaves on the reduction of total cholesterol in hypercholesterolemia mice. Extraction is carried out by the maceration method using 96% ethanol and produces a yield of 3.8%. A total of 36 male mice were divided into six groups (n=6): negative control, positive control (propylthiouracil induction), drug control (simvastatin), and three extract treatment groups with doses of 14, 28, and 56 mg/20 g BB. The treatment was given orally for four days, then cholesterol levels were analyzed using the enzymatic method CHOD-PAP. The results showed that the positive control cholesterol levels increased significantly (189.3 ± 6.2 mg/dL) compared to the negative control (112.7 ± 10.3 mg/dL). The administration of the extract lowered cholesterol levels gradually: 170.4 ± 6.3 mg/dL (10%), 159.6 ± 7.6 mg/dL (15.7%), and 147.3 ± 11.7 mg/dL (22.2%). Simvastatin decreased more (117.7 ± 12.5 mg/dL; 37.8%). It was concluded that bidara arabic leaf extract has antihypercholesterolemia potential with a multifactorial mechanism, although its effectiveness is lower than that of simvastatin.